Intertextuality of the Figurative Image in Some Quintets of Al-Busiri’s Al-Burda - Yaqub, Armiaa (El Omda in Linguistics and Discourse Analysis, 2018)
This article titled ''Metaphoric intertextuality in some epigrams of Burdatul Busiry" examines some selected epigrams of "Burda" by identifying some mechanisms of its exploitation of some poetic imagery of the (Burda) through metaphor icon. The research uses the intertextuality criticism approach to attain this aim as well as descriptive methods to achieve the objectives. some of the major findings of the research, after analyzing the statistical data gathered are as follow: i. The metaphor techniques doesn’t convey a total similarity between the original text and the second text. ii. The metaphor techniques expresses environmental, cultural and ideological differences of the two writers. iii Both two writers are indebted to the classical Arab Poets with regard to their poetic imagery. The most dominant metaphor technic between the two writers is (Attashbihul Balig)followed by (Attashbihi Attamsily).